Principal’s Strategy in Developing Teacher’s Professional Performance Competency to Improve Educational Quality - Nurlinayanti, Nurlinayanti; Arafat, Yasir; Putra, Muhammad Juliansyah (Journal of Social Work and Science Education, 2024)
This study aims to find out and analyze in depth the principal’s strategy in developing teacher professional performance competencies to improve education quality in SD Negeri 1 Koba Bangka Tengah while the discussion of this research focuses on (1) Principal leadership strategy steps; (2) Constraints faced in developing professional competence of teachers; (3) Model of developing professional competence of teachers which is suggested in the future in improving the quality of education. This research uses a descriptive qualitative approach with a phenomenological research type. Methods of data collection using the method of observation, interviews, and documentation. Data analysis techniques include data collection, data condensation, data presentation, and conclusion. The validity of the data was checked by using source triangulation and method triangulation techniques. Research informants are principals and teachers. The results of the study show that: (1) The strategic steps of the principal’s leadership in developing teacher competence to improve the quality of education are the first formal strategy, namely the teacher assigned by the institution to attend education and training, the second non-formal strategy is the teacher on their wishes and efforts to train and develop themselves related to their work or position; (2) There are several obstacles faced in developing teacher competence, namely the lack of or limited IT mastery by the teacher, the lack of teacher creativity in the learning process in the classroom, and the lack of scientific work made by the teacher; (3) The model that can be used to improve the competence of teachers in carrying out their duties is through In-service education or In-service training programs.